Factor studies into the determinants of memory accuracy and retention in air traffic situations – a statistical approach - Ng, June Ji Ying (Nanyang Technological University, 2022)
With the growing popularity of air travel and technological advancements in the aviation industry, it would be advantageous for Air Traffic Controllers (ATC) to work in the best possible condition. As a result, more research into the memory and information retention of humans is required. Much research on situational awareness and memory have been conducted. However, in this report, an eye tracker was employed in conjunction with a questionnaire with the goal of investigating the physiological factors linked with Levels 1 and 2 of the Endsley Model - information perception and comprehension. The reactions of the individuals would be crucial in determining how much information was noticed and remembered. The purpose of this report is to add to our present knowledge of ATC memory retention and accuracy while demonstrating the feasibility of employing this integrated technique to investigate situational awareness. It should be highlighted that with higher levels of situational awareness, the physiological factors discovered in this study may be different (projection). As a result, it is suggested that some components of this integrated technique be fine-tuned before applying it to the research of higher degrees of situational awareness (projection).